2001
DOI: 10.1136/ip.7.3.234
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of bias after data linkage of hospital admissions data to police road traffic crash reports

Abstract: Research question-Does a database of hospital admission data linked to police road traYc accident (RTA) reports produce less biased information for the injury prevention policymaker, planner, and practitioner than police RTA reports alone? Design-Data linkage study. Study population-Non-fatal injury victims of road traYc crashes in southern England who were admitted to hospital. Data sources-Hospital admissions and police RTA reports. Main outcome measures-The estimated proportion of road traYc crashes admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 13 publications
2
45
0
Order By: Relevance
“…Data collected by the Police indicate that number of injuries among pedestrians occurring each year in Poland on zebra crossing increased from 27% in 1998 to 29.8% in 2005. The police and in-hospital data vary, but the death and disability rates of injured pedestrians in Poland are enormously high (17,18,19). It is estimated that every 24 minutes one of them is killed or seriously disabled.…”
Section: Discussionmentioning
confidence: 99%
“…Data collected by the Police indicate that number of injuries among pedestrians occurring each year in Poland on zebra crossing increased from 27% in 1998 to 29.8% in 2005. The police and in-hospital data vary, but the death and disability rates of injured pedestrians in Poland are enormously high (17,18,19). It is estimated that every 24 minutes one of them is killed or seriously disabled.…”
Section: Discussionmentioning
confidence: 99%
“…Informations about road traffic crashes would be biased if the analizes were based solely on traffic police reports data, they are less biased if they derived from the hospital admissions linked database (Cryer et al, 2001 In some other studies in the world, the problems of road traffic accidents in urban area was shown. Hijar M et al (2004) emphasised the economic impact of road traffic accident in an urban area in Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…From the methodological point of view, database linkage of road traffic accidents was based on the experience of other authors in studies on mortality 15 and morbidity 14 . The strategy confirmed that the two data sources were complementary, by comparing them to the final linked database (BH10-SIM).…”
Section: Discussionmentioning
confidence: 99%
“…The urban health approach to road traffic accidents by linking and upgrading available databases allows comparing diverse sources 14,15 , thereby contributing to the implementation, development, and monitoring of integrated policies for the prevention of such accidents.…”
Section: Introductionmentioning
confidence: 99%